2010
DOI: 10.1108/14691931011064581
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual capital and value creation in Spanish firms

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(36 citation statements)
references
References 47 publications
2
27
0
3
Order By: Relevance
“…The findings of this study also supported with the previous studies such as (Abdullah & Sofian, 2012;Ahmad Sharabati et al, 2013;Bontis et al, 2000;Castro & Delgado-Verde, 2012;Díez et al, 2010;Khalique et al, 2011;Ngah & Ibrahim, 2009;Sharabati, Jawad, & Bontis, 2010). The findings of this study could be encouraged to the concerned authorities to explore and capitalize their intangible assets to enhance the performance of Islamic Banks operating in Malaysia.…”
Section: Discussion Recommendations and Future Studiessupporting
confidence: 89%
See 1 more Smart Citation
“…The findings of this study also supported with the previous studies such as (Abdullah & Sofian, 2012;Ahmad Sharabati et al, 2013;Bontis et al, 2000;Castro & Delgado-Verde, 2012;Díez et al, 2010;Khalique et al, 2011;Ngah & Ibrahim, 2009;Sharabati, Jawad, & Bontis, 2010). The findings of this study could be encouraged to the concerned authorities to explore and capitalize their intangible assets to enhance the performance of Islamic Banks operating in Malaysia.…”
Section: Discussion Recommendations and Future Studiessupporting
confidence: 89%
“…There is no doubt that there are many other important factors that contribute to enhance the performance of organizations but in a knowledge-based economy, many researchers such as (Bataineh & Al Zoabi, 2011;Bontis et al, 2000;Bueno, Salmador, & Rodríguez, 2004;Díez, Ochoa, Prieto, & Santidrián, 2010;Khalique, Shaari, & Isa, 2011;Ordonez de Pablos, 2004) have found that intellectual capital is one of the most important and strategic assets for the success of organizations. They argued that in a competitive business environment intellectual capital is considered as the life blood of knowledge intensive organizations.…”
Section: Introductionmentioning
confidence: 99%
“…According to this definition, J. M. Díez et al (2010) focused only on human capital and structural capital. Human capital was considered as the sum of knowledge, skills and experience that have employees in the company and structural capital was assumed as the amount of all structures and mechanisms that an employee can use in order to gain his goals.…”
Section: Intellectual Capital and Its Relation With The Company's Valmentioning
confidence: 99%
“…Value added Human capital Structural capital Díez et al (2010) Intellectual capital -related to value added and knowledge productivity.…”
Section: Value Added Human Capital Structural Capital Customer Capitalmentioning
confidence: 99%
See 1 more Smart Citation